Studi Retrospektif : Karakteristik Pemeriksaan Radiologi di RSU Bunda Thamrin Medan Periode Januari 2024 - Juli 2024 - Evita Sola Gracia (STIKES Columbia Asia Medan, 2024)
Background: Radiology plays a vital role in modern healthcare, offering diagnostic and therapeutic services. RSU Bunda Thamrin Medan provides comprehensive radiology services, ranging from X-ray to CT scan, MRI, and ultrasound. Objective: This study aims to analyze the characteristics of radiology examinations performed at RSU Bunda Thamrin Medan from January to July 2024. Methods: A retrospective, descriptive observational study was conducted. Data from 18,986 patients were collected from medical records, including age, gender, and type of examination. Results: X-ray was the most frequent examination (70.2%), followed by ultrasound (16.6%). Most patients were between 21-50 years of age, with a near-equal distribution between male and female patients. CT scan and MRI were used in more specific cases. Conclusion: X-ray and ultrasound dominate radiological examinations, reflecting their broad utility in diagnosis. CT and MRI, though less frequent, are crucial for complex cases. Continuous equipment maintenance and staff training are needed to support the increasing demand for radiology services.